(untitled) (PANGEEA, 2025)
Sustainable development is a complex and fundamental concept in current policy. It allows a nation to plan, to implement and monitor the progress of society, in view of achieving long-term objectives, of meeting the demands of the present generation without preventing the future generations from satisfying their own needs. The Romanian national sustainable development strategy was finalized in 1999 by a work group created through the Government Decision no. 305/1999. Although written in a participative manner, the strategy did not stipulate the adequate mechanism for implementation monitoring which can support its periodical revision. The present paper aims at highlighting the general lines that Romania, as a member state of the European Union, must consider. European developments intend to identify and extend actions that can lead to an improvement in life quality for the present and future generations, by sustainable communities that are capable of managing and using resources efficiently and of exploiting the ecological and social innovating potential of economy, thus ensuring prosperity, environmental protection and social cohesion.